Gender differentiated utilization of banana as food, medicine and cultural artefact in central Uganda - Mulugo, Lucy; Kyazze, Florence Birungi; Kibwika, Paul; Ngolobe, Emmanuel; Omondi, Bonaventure Aman Oduor; Kikulwe, Enoch (Informa UK Limited, 2024)
Gender roles exert significant influence on the utilization of agricultural resources globally, yet their impact is often overlooked in breeding programs. This study examines gender-specific banana utilization to guide breeding strategies. Conducted in central Uganda from January to March 2023, the study involved focus group discussions with 30 men and 30 women, and interviews with 10 key informants (4 men and 6 women), using a guided checklist. Content analysis was utilized to summarize, visualize and extract information on the use of bananas for food, medicine and cultural purposes. Findings reveal distinct gender preferences: men preferred high-yielding varieties with desirable traits like bunch and finger size, while women favored early-maturing cultivars with soft, tasty, and yellow matooke. The “Nakitembe” cultivar (AAA) emerged as pivotal for food, medicine, and cultural practices, alongside cultivars from the Mbidde clone set. The “Gonja” cultivar (AAB), plantain, held equal significance for food (roasted), medicine, and culture. Newly introduced cultivars were valued for food and local brew. Women exhibited greater knowledge of banana utilization for sustenance and medicine. Cultivars exhibiting early maturation, resilient to pests, diseases, and weather vagaries were preferred by both men and women for their sustenance, medicinal use and cultural significance. These findings underscore the complex interplay between banana cultivars, gender preferences, and the roles of men and women in food security, healthcare, and cultural practices. They are vital for breeders and policymakers to consider gender-specific needs and preferences in breeding and policy development.